Secretory phospholipase A(2)-IIA and cardiovascular disease: a mendelian randomization study - Holmes, Michael V; Simon, Tabassome; Exeter, Holly J; Folkersen, Lasse; Asselbergs, Folkert W; Guardiola, Montse; Cooper, Jackie A; Palmen, Jutta; Hubacek, Jaroslav A; Carruthers, Kathryn F; Horne, Benjamin D; Brunisholz, Kimberly D; et al. (Journal of the American College of Cardiology, 2013)
OBJECTIVES: This study sought to investigate the role of secretory phospholipase A2 (sPLA2)-IIA in cardiovascular disease. BACKGROUND: Higher circulating levels of sPLA2-IIA mass or sPLA2 enzyme activity have been associated with increased risk of cardiovascular events. However, it is not clear if this association is causal. A recent phase III clinical trial of an sPLA2 inhibitor (varespladib) was stopped prematurely for lack of efficacy. METHODS: We conducted a Mendelian randomization meta-analysis of 19 general population studies (8,021 incident, 7,513 prevalent major vascular events [MVE] in 74,683 individuals) and 10 acute coronary syndrome (ACS) cohorts (2,520 recurrent MVE in 18,355 individuals) using rs11573156, a variant in PLA2G2A encoding the sPLA2-IIA isoenzyme, as an instrumental variable. RESULTS: PLA2G2A rs11573156 C allele associated with lower circulating sPLA2-IIA mass (38% to 44%) and sPLA2 enzyme activity (3% to 23%) per C allele. The odds ratio (OR) for MVE per rs11573156 C allele was 1.02 (95% confidence interval [CI]: 0.98 to 1.06) in general populations and 0.96 (95% CI: 0.90 to 1.03) in ACS cohorts. In the general population studies, the OR derived from the genetic instrumental variable analysis for MVE for a 1-log unit lower sPLA2-IIA mass was 1.04 (95% CI: 0.96 to 1.13), and differed from the non-genetic observational estimate (OR: 0.69; 95% CI: 0.61 to 0.79). In the ACS cohorts, both the genetic instrumental variable and observational ORs showed a null association with MVE. Instrumental variable analysis failed to show associations between sPLA2 enzyme activity and MVE. CONCLUSIONS: Reducing sPLA2-IIA mass is unlikely to be a useful therapeutic goal for preventing cardiovascular events.
Keywords: genetics; drug development; Phospholipases A2, Secretory; sekreční fosfolipasy A2; odds ratio; mendelovská randomizace; sPLA(2); Humans; regulace genové exprese; Alleles; LDL-C; myocardial infarction; major vascular events; celosvětové zdraví; randomized clinical trial; lidé; confidence interval; CI; Global Health; OR; secretory phospholipase A(2); epidemiology; Mendelian Randomization Analysis; kardiovaskulární nemoci; low-density lipoprotein cholesterol; MVE; ACS; SNP; single-nucleotide polymorphism; cardiovascular diseases; Mendelian randomization; RCT; incidence; alely; DNA; Incidence; Gene Expression Regulation; Cardiovascular Diseases; acute coronary syndrome(s); MI